Speechless : the polar realm [videorecording (DVD)] - Sidey, Richard; Sidey, Richard (Filmhub, 2025)
Beautifully filmed by New Zealand nature photographer Richard Sidey over a decade throughout the Earth's polar regions, Speechless: The Polar Realm is a non-verbal visual meditation of light, life, loss, and wonder at the ends of the globe.